Analysis of The Effect of Population Density, Unemployment, Minimum Wage, and Human Development Index (IPM) on Criminality in North Sumatra - Widya Gustriani Harahap; Raina Linda Sari; Irsad Lubis (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The study aims to analyze the effect of population density, unemployment, minimum wage, inequality and human development index on crime in North Sumatra province. The type of research used in this study was descriptive research using quantitative research methods. The type of data used in this research is secondary data. In this study, Microsoft Excel Home and Student 2021 and Eviews 12 Student were used for data processing and hypothesis testing. The result of this study is that population density and Human Development Index has a positive and significant effect on crime. Unemployment has a positive and insignificant effect on crime. The Minimum Wage have a negative and insignificant effect on crime, and then Population Density, Unemployment, Minimum Wage, and Human Development Index together have an effect on crime in North Sumatra Province.